A Closer Look - Powzyk, Joyce (USA, 1990)
This bookIntroduces general ways animals camouflage themselves, such as coloration, mimicry, and disguise, and discusses how specific animals protect themselves using these techniques...
Keywords: Animal; Animal Camouflage; Juvenile Non-Fiction